81 LONGER CHAIR-STAND TIME IS ASSOCIATED WITH ORTHOSTATIC INTOLERANCE IN AN OLDER IRISH POPULATION. (18th November 2021) - Duggan, E; Knight, S; Rizzo, R; David, J; Kenny, R A; Romero-Ortuño, R
Abstract: Background: Hospital admissions for orthostatic hypotension (OH) have risen more than two-fold in the past ten years. OH can lead to orthostatic intolerance (OI), and both OH and OI are common causes of falls and injuries in older persons. Sarcopenia is also common in older persons and associated with adverse health outcomes. The 5-chair stand test (5-CST) can be used as a marker of sarcopenia and a cut-off of 15 s has been proposed. We hypothesized that those with a worse performance on the 5-CST would be at greater risk of OH and sought to investigate this in an older Irish population cohort study. Methods: 5-CST was measured in keeping with a standardised protocol. Beat-to-beat blood pressure was measured with the Finometer device according to the active stand protocol. Multivariable logistic regressions were performed to investigate the associations between OH at 40 seconds after standing (OH40), OI (dizziness after standing), and 5-CST time. Potential confounders were controlled for in the model including age, sex, education, body mass index and medications. Results: Data from 3, 119 participants were available for analysis. Mean age was 63.8 years, 55% were female, 25% took longer than 15s on the 5-CST and mean baseline blood pressure was 141/76 mmHg. Proportion of OH40 was 12.5% and 4.4% reported OI. In the multivariable model, OH40 was not independently associated with 5-CST time after controlling for age (p > 0.05). Worse performance on the chair stands test was however an independent predictor of OI (odds ratio 1.06, p = 0.039). Conclusion: Longer time taken on the 5-CST, a marker of sarcopenia, was an independent predictor of OI in a large population study. The relationship between sarcopenia and orthostatic blood pressure response is not well elucidated. We plan to further investigate this area in a future clinical cohort.